2021
DOI: 10.3390/ma14123332
|View full text |Cite
|
Sign up to set email alerts
|

Action Mechanisms of Curcumin in Alzheimer’s Disease and Its Brain Targeted Delivery

Abstract: AD is a chronic neurodegenerative disease. Many different signaling pathways, such as Wnt/β-catenin, Notch, ROS/JNK, and PI3K/Akt/mTOR are involved in Alzheimer’s disease and crosstalk between themselves. A promising treatment involves the uses of flavonoids, and one of the most promising is curcumin; however, because it has difficulty permeating the blood–brain barrier (BBB), it must be encapsulated by a drug carrier. Some of the most frequently studied are lipid nanocarriers, liposomes, micelles and PLGA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 179 publications
1
24
0
Order By: Relevance
“…In addition, curcumin attenuated the oxidative stress in a streptozotocin (STZ)-induced model by enhancing reduced glutathione (GSH) content and reducing the acetylcholinesterase activity in the hippocampus and cerebral cortex [22,23]. Previous studies showed that curcumin increased lifespan and decreased amyloid neurotoxicity in an invertebrate model [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, curcumin attenuated the oxidative stress in a streptozotocin (STZ)-induced model by enhancing reduced glutathione (GSH) content and reducing the acetylcholinesterase activity in the hippocampus and cerebral cortex [22,23]. Previous studies showed that curcumin increased lifespan and decreased amyloid neurotoxicity in an invertebrate model [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, however, has certain disadvantages too, which includes its low water solubility and bioavailability. Dissolving it into organic solvent improves it solubility but its absorption remains poor (Ege, 2021;Jia et al, 2021). Some recent articles addressed the methods to enhance curcumin's effectiveness in treating AD (Fan et al, 2018;Francesco et al, 2019;Ege, 2021).…”
Section: Curcumin Unfolded Protein Response and Neurodegenerative Diseases: A Trivial Connection And Future Perspectivesmentioning
confidence: 99%
“…Dissolving it into organic solvent improves it solubility but its absorption remains poor (Ege, 2021;Jia et al, 2021). Some recent articles addressed the methods to enhance curcumin's effectiveness in treating AD (Fan et al, 2018;Francesco et al, 2019;Ege, 2021). In future curcumin compounds must be chemically screened on target enzymes and proteins to facilitate more information.…”
Section: Curcumin Unfolded Protein Response and Neurodegenerative Diseases: A Trivial Connection And Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that the clinical symptoms of AD are divided into memory and cognitive impairments, accompanied by reduced self-care ability and abnormal mental manifestations while its aetiology and pathogenesis are still not fully understood. 2,3 Furthermore, the pathological features of AD are the presence of senile plaques and neurofibrillary tangles in the brain, while its proposed pathogenic mechanisms mainly include cholinergic dysfunction, the tau protein hyperphosphorylation hypothesis, the Aβ cascade hypothesis and the oxidative stress hypothesis. [4][5][6] Nevertheless, the current drug pipeline for AD in clinical trials remains dry, as cholinesterase inhibitors and glutamate receptor antagonists only ameliorate symptoms and do not cure the disease.…”
Section: Introductionmentioning
confidence: 99%